Characterization and stability of short-chain fatty acids modified starch Pickering emulsions. (15th July 2020) - Abdul Hadi, N.; Marefati, A.; Matos, M.; Wiege, B.; Rayner, M.
Highlights: Rice and quinoa starch were esterified by short-chain fatty acids. Increasing starch concentration led to reduced emulsion droplets size. Increasing modification level and chain length improved emulsifying capacity. SCFA-quinoa starch emulsions had better stability than rice over 50 days storage. Abstract: Acetylated, propionylated and butyrylated rice and quinoa starches at different levels of modification and starch concentrations, were used to stabilize oil-in-water starch Pickering emulsions at 10% oil fraction. Short-chain fatty acid modified starch Pickering emulsions (SPEs) were characterized after emulsification and after 50 days of storage. The particle size distribution, microstructure, emulsion index, and stability were evaluated. An increase in starch concentration led to a decrease of emulsion droplet sizes. Quinoa starch has shown the capability of stabilizing Pickering emulsions in both the native and modified forms. The emulsifying capacity of SPEs was improved by increasing the chain length of SCFA. Modified quinoa starch with higher chain lengths (i.e. propionylated and butyrylated), at higher levels of modification, showed higher emulsion index (>71%) and stability over the entire 50 days storage. At optimized formulation, SCFA-starch particles have the potential in stabilizing emulsions for functional foods, pharmaceutical formulations, or industrial food applications.